Bipolaris hawaiiensis (Bugnicourt ex M.B. Ellis) Uchida & Aragaki - A new record of human pathogenic species of Bipolaris in Bangladesh (Dhaka University Journal of Biological Sciences, 2013)
Abstract not availableDhaka Univ. J. Biol. Sci. 22(2): 175-178, 2013 (July)